Transcription factor Hap2p regulates antioxidant stress responses to maintain miconazole resistance in Candida albicans - Yulin Qin; Quanzhen Lv; Hongtao Xu; Yongbing Cao; Bing Han (Mycology)
Acquired resistance in Candida albicans brings about a serious challenge to the clinical application of azoles, so it is urgent to elucidate the mechanisms of azole resistance to improve the therapeutic efficiency. In the aim of searching for the potential targets mediating fluconazole resistance, we screened a mutant library of 48 transcription factor deletion Candida albicans strains. The screening results showed that hap2Δ/Δ mutants were significantly more susceptible to azoles, especially to miconazole (MCZ). Under MCZ treatment, the intracellular reactive oxygen species (ROS) were significantly higher in hap2Δ/Δ mutants compared to the control strain SN250. The addition of antioxidants reversed the MCZ-sensitive phenotype caused by the deletion of HAP2. Consistently, the expression of antioxidases responsible for scavenging ROS was shown to decrease in hap2Δ/Δ mutants, suggesting that the transcription factor Hap2p is involved in the regulation of oxidative stress responses in C. albicans. In addition, HAP2 deficiency also resulted in impaired mitochondrial function and affected cellular energy supply, which may be related to the iron deficiency regulated by HAP complex. HAP2 disruption also decreased efflux-mediated resistance of C. albicans, as demonstrated by a significant decrease in Cdr1p expression and a slight decrease in Mdr1p expression in hap2Δ/Δ strains under the action of MCZ. The above results indicate that the transcription factor Hap2p was required for the resistance of C. albicans to azoles, which could provide a new strategy to solve the clinical azoles resistance.